Intensity and Prevalence of Ectoparasites in Mangrove Crabs (Scylla serrata) Desa Deah Raya Village, Syiah Kuala University, Banda Aceh City - Nisa, Nurian; Akbar, Said A.; Perdana, Adli W.; Aleid, Layan KM.; Wikurendra, Edza A. (Narra X, 2024)
Mangrove crab (Scylla serrata) is a fishery commodity that has high economic value. The supply of mangrove crabs in Indonesia is still dominated by wild catches. One of the places to catch mangrove crabs in Banda Aceh City is the Mangrove Area of ​​Deah Raya Village, Syiah Kuala District. Mud crabs are very susceptible to infestation by pathogens in their environment. Pathogens that are often found infesting mud crabs are parasites. Ectoparasite attacks are very dangerous for mud crabs because they can cause damage to the body organs of mud crabs. Therefore, this research was conducted to determine the level of intensity and prevalence of ectoparasites in mud crabs (Scylla serrata) caught by fishermen in Deah Raya Village. This research uses a survey method with a purposive sampling method. Ectoparasite examination is carried out using the smear method. This research was conducted at the Hatchery Laboratory of the Faculty of Maritime Affairs and Fisheries in May 2024. Mangrove crabs (Scylla serrata) were studied by 30 individuals. The results of the observations found types of ectoparasites from the protozoa phylum, namely Zoothamnium sp, Epistylis sp, Vorticella sp, and from the arthropod phylum Octolasmis sp. The prevalence value of the type of ectoparasite that infests Scylla serrata is Zoothamnium sp (50%) infection "very often" Epistylis sp (20%) infection "often" Vorticella sp (10%) infection "often" Octolasmis sp (10%) infection "often" The intensity value of the type of ectoparasite that infests Scylla serrata is Zoothamnium sp. (7.5 ind/head) "Medium" infection Epistylis sp. (5 ind/head) "Low" infection Vorticella sp.(2ind/head) "Low" infection and Octolasmis sp.(1 ind/head) "Low" infection ”